New data on Iris pskemensis and its placement in Alatavia (Iridaceae) - Crespo, Manuel B.; Martínez-Azorín, Mario; Mavrodiev, Eugeny V. (Phytotaxa, 2017)
Iris pskemensis Rukšāns (2007: 363) was described on the basis of materials collected near Ihnachsai (Ikhnachsay) in the higher areas of Pskem mountain range (eastern Uzbekistan), which were propagated in Latvia. In the short protologue it was placed in Iris subg. Hermodactyloides Spach (1846: 16) and was briefly compared to I. kolpakowskiana Regel (1878: 263) and I. winkleri Regel (1883: 677), the two known members of I. sect. Monolepis (Rodionenko 1961: 205) Mathew (1989a: 87). However, in the recent comprehensive arrangement of the ‘Iris flower clade’, Crespo et al. (2015) transferred it into Iridodictyum Rodionenko (1961: 201).